Association of β-Amyloid and Basal Forebrain With Cortical Thickness and Cognition in Alzheimer and Lewy Body Disease Spectra. (1st March 2022) - Yoo, Han Soo; Jeon, Seun; Cavedo, Enrica; Ko, MinJin; Yun, Mijin; Lee, Phil Hyu; Sohn, Young H.; Grothe, Michel J.; Teipel, Stefan; Hampel, Harald; Evans, Alan C.; Ye, Byoung Seok
Abstract : Objective: Cholinergic degeneration and β-amyloid contribute to brain atrophy and cognitive dysfunction in Alzheimer disease (AD) and Lewy body disease (LBD), but their relationship has not been comparatively evaluated. Methods: In this cross-sectional study, we recruited 28 normal controls (NC), 55 patients with AD mild cognitive impairment (MCI), 34 patients with AD dementia, 28 patients with LBD MCI, and 51 patients with LBD dementia. Participants underwent cognitive evaluation, brain MRI to measure the basal forebrain (BF) volume and global cortical thickness (CTh), and 18 F-florbetaben (FBB) PET to measure the standardized uptake value ratio (SUVR). Using general linear models and path analyses, we evaluated the association of FBB-SUVR and BF volume with CTh or cognitive dysfunction in the AD spectrum (AD and NC) and LBD spectrum (LBD and NC), respectively. Covariates included age, sex, education, deep and periventricular white matter hyperintensities, intracranial volume, hypertension, diabetes, and hyperlipidemia. Results: BF volume mediated the association between FBB-SUVR and CTh in both the AD and LBD spectra, while FBB-SUVR was associated with CTh independently of BF volume only in the LBD spectrum. Significant correlation between voxel-wise FBB-SUVR and CTh was observed only in the LBD group. FBB-SUVR was independently associated with widespread cognitive dysfunction in both the AD and LBD spectra, especially in the memory domain (standardized beta [B] for AD spectrum = −0.60, B for LBD spectrum = −0.33). In the AD spectrum, BF volume was associated with memory dysfunction (B = 0.18), and CTh was associated with language (B = 0.21) and executive (B = 0.23) dysfunction. In the LBD spectrum, however, BF volume and CTh were independently associated with widespread cognitive dysfunction. Conclusions: There is a common β-amyloid–related degenerative mechanism with or without the mediation of BF in the AD and LBD spectra, while the association of BF atrophy with cognitive dysfunction is more profound and there is localized β-amyloid–cortical atrophy interaction in the LBD spectrum.